Our Vanishing Wildlife - Tiwari, K. M. (Indian Forester, 1991)
Our civilization and heritage as well as our scriptures enjoin upon us to protect and preserve all life forms. Yet, the scenario that confronts us is bleak, with many wildlife species on the brink of extinction and many habitats destroyed due to untrammelled clearing of forests. While National Parks and Sanctuaries have had a beneficial impact, these too are under severe biotiC pressures. The author calls for winning over the people in order to protect and preserve wildlife.